PENGARUH PERSEPSI SISWA TENTANG KOMPETENSI GURU EKONOMI DAN LINGKUNGAN SEKOLAH TERHADAP HASIL BELAJAR SISWA KELAS XI IPS SMA NEGERI 2 MALANG PADA MATA PELAJARAN EKONOMI TAHUN AJARAN 2015/2016 - Reizky Rino Dwi Prasetyo; Achmad Ali Wafa; Ro'ufah Inayati (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2016)
Teacher has an important role in learning process. The teacher is good teacher if he/her has ability or competence such as a set of capabilities can realize their professional performance. In addition, the school environment also plays an important role for the development of students' learning. The students 11 IPS Grade SMA Negeri 2 Malang learning result are included into low learning result because they lack of motivation to study. The lack of enthusiasm for learning is due to the teachers who are constantly using less varied learning model that makes students become bored and less concentrating while studying. The other thing is the fatigue caused by the long duration of the school which is not matched by adequate rest hours. This causes students to become lazy to learn and give the impact on learning result become low. This research used quantitative approach with explanation type. Data analysis that used in this research was multiple linear regression analysis. Based on data analysis result, it could be concluded: (1) there was positive and significant effect students perception about competence of economics teacher to the learning result on economy subject, (2) there was positive and significant effect students perception about school environment to the learning result on economy subject, and (3) there was positive and significant effect students perception about competence of economics teacher and school environment to the learning result on economy subject.